2023
DOI: 10.1111/1471-0307.12951
|View full text |Cite
|
Sign up to set email alerts
|

Technological solutions and adaptive processing tools to mitigate the impact of seasonal variations in milk composition on Cheddar cheese production—A review

Abstract: Variability in milk composition and physicochemical properties impact both manufacturing process performance and the end‐use functionality of cheese. Such variability may be attributed to seasonal calving patterns, production systems, breed, weather patterns, and feed type and significantly impacts concentrations of macro‐ and microconstituents and ultimately cheese composition and quality. This article reviews technological approaches (e.g., milk standardisation protocols and calcium addition), and predictive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 92 publications
(195 reference statements)
0
1
0
Order By: Relevance
“…In milk, near-infrared light scattering is directly related to the speed of micellar aggregation and gel hardening, so this optical sensor technology has been proven as a valuable tool to control milk coagulation [10]. In particular, the fiber optic sensor near-infrared (NIR) scattering, CoAguLite, is an inline sensor that has been well-documented for monitoring milk coagulation and predicting gelation and cutting times [11] and is currently commercially available for inline control in cheesemaking, mainly in the United States. Several previous studies have shown that such a sensor is a promising instrument for inline monitoring of optical properties during milk coagulation, providing indirect information on relevant technological parameters in cheese production.…”
Section: Introductionmentioning
confidence: 99%
“…In milk, near-infrared light scattering is directly related to the speed of micellar aggregation and gel hardening, so this optical sensor technology has been proven as a valuable tool to control milk coagulation [10]. In particular, the fiber optic sensor near-infrared (NIR) scattering, CoAguLite, is an inline sensor that has been well-documented for monitoring milk coagulation and predicting gelation and cutting times [11] and is currently commercially available for inline control in cheesemaking, mainly in the United States. Several previous studies have shown that such a sensor is a promising instrument for inline monitoring of optical properties during milk coagulation, providing indirect information on relevant technological parameters in cheese production.…”
Section: Introductionmentioning
confidence: 99%